HELPERKU: INNOVATIVE E-COMMERCE APPLICATIONS AS BUSINESS SOLUTIONS FOR PEOPLE WITH DISABILITIES - Yenita, Yenita; Wijaya, Septihani Michella (Graduate Program of Universitas Tarumanagara, 2023)
HELPERKU is an innovative e-commerce application where product sales carried out by Persons with Disabilities are designed with 4.0-based display device features. HELPERKU is here to provide convenience for everyone who has limitations but wants to start a business or already has a business to be able to gain knowledge and share experiences about their business through attractive supporting features. The strategy analysis tools used are SWOT Analysis, PESTLE, 4P, and Five Force’s Porter Analysis. HELPERKU will be downloaded via Google Play Store and App Store, making it easier for mobile/android users. Jakarta is the first location for HELPERKU to operate its application. The presence of HELPERKU is expected to become a large application company that can be useful for users, especially people with disabilities, investors, as well as a medium for experimenting in terms of knowledge, practical learning, and affordable business consulting with the presence of experienced experts and figures in the field of business. It is hoped that after the HELPERKU application, people who want to start a business can experience business expansion in a relatively short time. HELPERKU is still a relatively new application, but HELPERKU opens opportunities for investors to invest with collateral in a relatively short time, which is two years and five months with an annual discount rate of 7% and return on investment of 20%. HELPERKU earnings during this period are normal for new app companies.